Fracture in living tissues. Issue 6 (June 2022) - Bonfanti, Alessandra; Duque, Julia; Kabla, Alexandre; Charras, Guillaume
Abstract : During development and in adult physiology, living tissues are continuously subjected to mechanical stresses originating either from cellular processes intrinsic to the tissue or from external forces. As a consequence, rupture is a constant risk and can arise as a result of excessive stresses or because of tissue weakening through genetic abnormalities or pathologies. Tissue fracture is a multiscale process involving the unzipping of intercellular adhesions at the molecular scale in response to stresses arising at the tissue or cellular scale that are transmitted to adhesion complexes via the cytoskeleton. In this review we detail experimental characterization and theoretical approaches for understanding the fracture of living tissues at the tissue, cellular, and molecular scales. Highlights: Living tissue fracture is a multiscale phenomenon. Fracture can occur as a result of externally applied stresses or through active stresses generated by myosin motors. Microelectromechanical systems (MEMS) enable the characterization of fracture at the molecular, cellular, and tissue scales.